ISSP. An experiment in multi-systemic responses to persistent young offenders known to children's services - Bullock, Roger; Van der Laan, Peter (The British journal of criminology, 2004)
ISSP is a multi-systemic intervention for persistent young offenders delivered jointly by police, social services and education. Based on a Netherlands programme, a variation of the approach has been widely adopted in England and Wales. The intervention has seven components including close supervision by police, family group conferences, multi-agency reviews and opportunities for reparation and mentoring. To qualify, young people need at least three convictions or cautions, to be aged 15-17 and to have experienced custody or a failed community sentence. Candidates were randomly allocated to either ISSP or two control groups. As hypothesized, reconviction rates were unaffected by the intervention but there was a 30 to 50 per cent reduction in the volume of crime committed by ISSP participants. No particular aspect of the programme was associated with success suggesting a general placebo effect. Lessons for the planning and administration of such projects and the need for improved epidemiological data about persistent offenders are indicated